Sero types, phage types and antibiotic susceptibilities of Salmonella strains isolated from horses in The Netherlands from 1993 to 2000 - van Duijkeren, E.; Wannet, W.J.B.; Heck, M.E.O.C.; van Pelt, W.; Sloet van Oldruitenborgh-Oosterbaan, M.M.; Smit, J.A.H.; Houwers, D.J. (Veterinary microbiology, 2002)
We studied 232 Salmonella strains from horses with salmonellosis in The Netherlands, isolated in the period from 1993 to 2000 in order to provide insight in the dynamics of sero-, phage types (pt) and antibiotic susceptibilities over time. The strains were tested for susceptibility to seven antimicrobial agents using the agar diffusion method. In addition, the isolates were sero typed and Salmonella enterica subspecies enterica Typhimurium and Enteritidis strains were further phage typed. S. Typhimurium strains of phage type 506 and 401 (both classified as DT 104 in the English phage typing system) were additionally tested for their susceptibility to chloramphenicol (C), streptomycin (S) and sulfonamides (Su). Resistance was common against tetracycline and ampicillin. Most strains were susceptible to enrofloxacin (Enr) and ceftiofur (Cef). Resistance to tetracycline (T), kanamycin (K), ampicillin (A) and trimethoprim/sulfonamide (Sxt) combinations decreased from 1993 to 2000, whereas the resistance to gentamicin (G), ceftiofur and enrofloxacin was stable over time. S. Typhimurium was the predominant serovar and showed more (multiple) resistance compared to other Salmonella serovars. Sixteen different resistance patterns were found, with resistance to T alone and the combination of ACSSuT and AKSxtT being the most common. The multiresistant S. typhimurium phage type 506 (DT 104) was the most common phage type isolated from horses and most of these strains showed the pentadrug resistance pattern ACSSuT. The S. Typhimurium phage type 401 (DT 104) was also found frequently with an ASSuT resistance pattern. The most common S. Typhimurium phage types in horses corresponded with those found in humans, pigs and cattle in the same period in The Netherlands.